Socio-environmental crime in Maceió resulting from the exploitation of rock salt - Pinho, Luana Cavalcante (Argumentum, 2024)
The article investigates socio-environmental crime resulting from rock salt mining in Maceió, Alagoas. It is supported by bibliographic sources that analyse Alagoas’s economy — focusing mainly on the state’s chemical industry — and documents covering various aspects of the crime. The paper traces the history of the chemical industry’s implementation in Alagoas, revealing that the environmental risks from the activity were disregarded despite early awareness. This led to the evacuation of the affected region and the displacement of approximately 60 thousand people. The article also examines the developments of the Financial Compensation and Relocation Support Programme, designed to compensate those directly affected by the crime. The majority of the affected population sought resettlement in other neighbourhoods of Maceió and its metropolitan region, contributing to inflated property prices in the city.